1 Corinthians 7 in the Light of the Jewish Greek and Aramaic Marriage and Divorce Papyri - Instone-Brewer, David (Tyndale bulletin, 2001)
The first half of this study explored 1 Corinthians 7 in the light of the Graeco-Roman Greek and Latin marriage and divorce papyri.1 These papyri showed that much of 1 Corinthians 7 has its basis in Graeco-Roman vocabulary and social structures. The believers at Corinth were facing the problem that divorce under Graeco-Roman law was legally complete when the dowry was returned and the couple separated. Comparisons with Jewish marriage and divorce papyri show that the lifestyle and morals that Paul wishes the Corinthians to adopt are based primarily on the Jewish interpretation of the Old Testament. This is illustrated from both Greek Jewish papyri, which show a Judaism thoroughly embedded in the Graeco